(untitled) (Journal of Pakistan Orthopaedic Association, 2015)
Objective: To evaluate the functional outcome of surgical relocation of congenital knee dislocation with or without arthrogryposis in age group over six months age. Methods: A descriptive study conducted in Paediatric Orthopaedic Clinic at Jinnah Postgraduate Medical Centre Karachi from January 2004 to December 2012. The patients with congenital dislocated knees type III (complete dislocation), over the age of 6 months to 5 years, having isolated Knee dislocation, knee dislocations with Hip dislocation and clubfoot were included as group A. The knee dislocations as a part of arthrogrypotic contractures were included as group B. Patients with paralytic disorders, arthrogryposis unable to sit due to poor muscle functions were excluded. Open reduction of Knee through dorsal midline incision and Quadriceps V-Y plasty. Relocated Knees were stabilized with Plaster of Paris cast, in 70Â° flexion of knee for 5-6 weeks, with scoring system for knee functions described by Ferris and Aichron. Results:Recurrent stiffness with poor results observed in 6 patients (12 knees) with group B, fair in 5 patients (10 knees) and none behaved good or excellent. In-group A (Knee dislocations with or without hip dislocation and clubfoot) results were Good to Excellent in 22 patients (36 knees), fair in 4 (7 knees) and poor with recurrence of severe stiffness in 1patient (7 knees). Conclusion: The results of surgery were excellent in isolated congenital knee dislocations, satisfactory in dislocated knees associated with clubfoot and dislocated hips. The outcome was less promising in Arthrogryposis (Amyoplasia) and in older walking age groups. Key Words: Arthrogryposis, Congenital, Dislocation, Isolated, Knee.